2002
DOI: 10.1002/pros.10146
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and apoptotic effects of silibinin in rat prostate cancer cells

Abstract: This study demonstrates that silibinin as well as silymarin induce growth inhibition and apoptosis in rat PCA cells. These results form a strong rationale for PCA prevention and therapeutic intervention studies with silibinin and silymarin in animal models, such as the MNU-testosterone rat PCA model, to establish their efficacy and to further define their mechanisms of action under in vivo conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…The viability of the cells was determined using the trypan blue dye exclusion assay, in which the color changes reflected the dead cells (13). In brief, the cells (1x10 4 /ml) were first seeded in the cell culture flask (each concentration in triplicate).…”
Section: Plant Materials and Extraction And Isolation Of Ttb2mentioning
confidence: 99%
“…The viability of the cells was determined using the trypan blue dye exclusion assay, in which the color changes reflected the dead cells (13). In brief, the cells (1x10 4 /ml) were first seeded in the cell culture flask (each concentration in triplicate).…”
Section: Plant Materials and Extraction And Isolation Of Ttb2mentioning
confidence: 99%
“…Recently, several studies with the antioxidant vitamin E and the polyphenolic flavonoid silibinin showed similar results concerning their anti-proliferation effects on PCA cells. The signaling pathway includes elevation in the hypophosphorylated form of pRb at the expense of the phosphorylated form of Rb, reduction at the protein level of CDKs, and cyclin typical to G1 phase of the cell cycle together with enhanced expression of the CDK inhibitor p21 cip1 [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemicals in parsley can slow the speed of cell division, leaving time for the cell to correct DNA mistakes and activate apoptosis and inhibit the migration of cancer cells. Considerable research shows that the flavonoid apigenin, found in celery, artichokes, and parsley may well be a key agent for killing breast, pancreatic, and numerous other cancer cell lines [23]. For example, 2015 research found apigenin to inhibit the growth of breast cancer cells, including HER2-positive ones [24].…”
Section: Parsleymentioning
confidence: 99%